Pengobatan Alternatif Tradisional Untuk Mencegah Penularan Covid-19 Menurut Perspektif Hukum Kekayaan Intelektual Di Kota Ambon - Ronald Saija; Teng Berlianty; Pieter Radjawane (SASI, 2021)
The success of vaccine development, one of the experiments to cure this virus, namely Traditional knowledge for most people has an important role for food security and the health of millions of people in developing countries. The purpose of this study was to determine and analyze the important role of the creator of traditional alternative medicine concoctions to prevent the transmission of Covid 19 in Ambon City, and the form of legal institutions by the Maluku Provincial Government to grant patents to the creators of traditional alternative medicine concoctions as local wisdom in handling treatment to prevent transmission. covid 19 in Ambon city. This research was conducted using an empirical juridical approach which is a descriptive study of qualitative analysis. The results showed that people in developing countries depend a lot on traditional medicine for up to 80% of their health needs. In addition, knowledge about health plants has become a source of modern medicine. The importance of the Government and society's attention to traditional knowledge and technology systems in Indonesia, especially in the field of herbal medicine. The occurrence of various polemics that often occur in the lives of indigenous peoples related to traditional healing for patients to prevent Covid-19 transmission in Ambon City.